Bitácora inconclusa de un sueño - Darío Rivera M., Álex (Oltreoceano - Rivista sulle migrazioni, 2021)
Asistimos a un poema en verso de tres actos. Primero, un inventario de lo cotidiano ante la necesidad de asumir el recoveco donde se habita ante la ausencia de una patria evocada y añorada. El segundo, evidencia cierto ostracismo buscando los escenarios dignos que, del otro lado, la otra patria nos niega. Y el último, invitación abierta a casa, a esa patria-matria donde puedan abrevar las esperanzas. Unfinished Log of a Dream In this three-act verse poem, the poet first makes an inventory of everyday life when faced with the need to consider an inhabited space as home while confronting the absence of the much evoked and longed-for homeland. inherent in the search for the worthy scenarios that, on the other side, the other country denies us. The third act is an open invitation to home, to that homeland-motherland where hopes can be nourished.